2016
DOI: 10.1016/j.fertnstert.2015.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Survey assessing obesity policies for assisted reproductive technology in the United States

Abstract: Centers that have policies regarding obesity and access to ART consider efficacy, procedural safety, safety in pregnancy, and overall health status. Policies vary widely. The patient's autonomy must be balanced with nonmaleficence and the avoidance of interventions that may be unsafe both immediately and long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 13 publications
(12 reference statements)
0
19
0
Order By: Relevance
“…Moreover, Koning et al (2010) suggested that overweight and obesity in ovulatory infertile women leads to a 44% and 70% increase in costs due to pregnancy complications, respectively. A recently published study by Kaye et al (2016) suggested how relevant it is to develop reasonable standards of care for obese patients, to encourage them to lose weight before undergoing fertility treatment, giving priority to safety and overall health status, although patient's autonomy must be balanced with non-maleficence and the avoidance of interventions that may be unsafe both immediately and in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Koning et al (2010) suggested that overweight and obesity in ovulatory infertile women leads to a 44% and 70% increase in costs due to pregnancy complications, respectively. A recently published study by Kaye et al (2016) suggested how relevant it is to develop reasonable standards of care for obese patients, to encourage them to lose weight before undergoing fertility treatment, giving priority to safety and overall health status, although patient's autonomy must be balanced with non-maleficence and the avoidance of interventions that may be unsafe both immediately and in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…The Royal Australian and New Zealand College of Obstetricians and Gynaecologists have published guidance that a BMI over 35 should be regarded as an absolute contraindication for IVF [ 56 , 57 ]. In the absence of professional body guidelines, a 2016 survey of providers of fertility services in the United States found that the majority of responding centres have a formal policy of setting a maximum BMI threshold for IVF [ 18 ]. A draft report from the Canadian Fertility and Andrology Society does not recommend imposing a BMI cutoff, though notes that there is significant appetite for this, and that a 2014 survey of Canadian medical directors found that 50% of respondents imposed a cut-off [ 7 , 24 ].…”
Section: Policy Guidance and Exclusion Of People With Obesitymentioning
confidence: 99%
“…In both women who conceive spontaneously and those who conceive using reproductive technology, the rate of conception is lower in women with obesity than normal weight counterparts . While most obstetric care providers have policies around the care of women with obesity during pregnancy, there is significant variation in how fertility clinics manage obesity . A study of fertility centres in the United States reported that 16% had no policy regarding obesity, while 21.4% did not offer in vitro fertilization to women with BMI >35‐40 kg/m 2 …”
Section: Rationale For the Management Of Obesity Prior To Conceptionmentioning
confidence: 99%
“…While most obstetric care providers have policies around the care of women with obesity during pregnancy, there is significant variation in how fertility clinics manage obesity . A study of fertility centres in the United States reported that 16% had no policy regarding obesity, while 21.4% did not offer in vitro fertilization to women with BMI >35‐40 kg/m 2 …”
Section: Rationale For the Management Of Obesity Prior To Conceptionmentioning
confidence: 99%